Mobile Application FaceFood Cafe: Aplikasi Restoran Face Food Cafe - Soble, Nurul Farhana; Ts. Dr. Azizul Azhar Ramli (Applied Information Technology And Computer Science, 2022)
The FaceFood Café Restaurant application is an application that works for customers to order food through online platform. Nowadays the restaurant business is growing in line with the development of technology. The restaurant business has many customers, yet still uses manual methods. The purpose of this application system is to overcome the problem of customers who are so busy and there is no time to visit a restaurant to buy food. The project has chosen an object -oriented approach to present and analyzed the data. In addition, by using this application, the ordering process will run smoothly. The system allows customers to order food then the order will be received by the restaurant administrator. The restaurant administrator will accept customer orders. Next the customer will receive the status of the order that has been placed. To complete the ordering process, the app allows administrators to add menus, delete menus, and modify menus. Through this application the customer can select an order through the menu list received by customer android application. Administrators can update the menu quickly and administrator errors in recording customer orders can be reduced. The advantage of the Face Food Cafe Restaurant application is that customers only need to make food orders using the Android smartphone more quickly, easily and comfortably and restaurant administrators do not have to incur costs to record customer orders and print menu brochures.